Finite-time matrix projective synchronization of fractional-order memristor-based delayed neural networks with parameter uncertainty - Xu, Shangbin; Hu, Bo; Zhang, Hai; Chen, Xinbin; Cao, Jinde (Nonlinear Analysis: Modelling and Control, 2026)
This research examines the phenomenon of finite-time matrix projective synchronization (FTMPS) in the context of two distinct fractional-order memristor-based delayed neural networks (FOMDNNs). For the FOMDNNs with indeterminate parameters, some suitable controllers are structured, and sufficient conditions for implementing the FTMPS are demonstrated through some inequality techniques and relevant lemmas pertaining to fractional calculus. The synchronization issues under two different norm cases are fully considered. Subsequently, two numerical examples of the FTMPS are revealed and the discrepancies in their synchronization gradually tend to zero, which shows the validity and accuracy of the obtained synchronization results.